KEGAWATDARURATAN SYOK HIPOVOLEMIK - Enita Dewi; Sri Rahayu (Universitas Muhammadiyah Surakarta, 2009)
Hypovolemic shock occurs when there is a loss of intravascular fluid volume. In hypovolemic shock the volume is inadequate to fill the vascular space. The most common cause of hypovolemic shock is hemorraghe (an excessive loss of whole blood). The amount of blood loss that results in shock depends on the efficiency of a person’s compensatory mechanism and the rapidity of blood loss. Signs and symptoms of hypovolemic shock should be monitored by nurses periodically. As a nurse, she should understands and has capability to handle this condition, in every place/ward. The nurses have to give appropriate interventions or emergency management for treat it.